Application of Microfluidic Chips in Separation and Analysis of Extracellular Vesicles in Liquid Biopsy for Cancer - Lu, Jin (Micromachines (Basel), 2019)
Extracellular vesicles (EVs) are becoming a promising biomarker in liquid biopsy of cancer. Separation EV from cell culture medium or biofluids with high purity and quality remains a technique challenge. EV manipulation techniques based on microfluidics have been developed in the last decade. Microfluidic-based EV separation techniques developed so far can be classified into two categories: surface biomarker-dependent and size-dependent approaches. Microfluidic techniques allow the integration of EV separation and analysis on a single chip. Integrated EV separation and on-chip analysis have shown great potential in cancer diagnosis and monitoring treatment of responses. In this review, we discuss the development of microfluidic chips for EV separation and analysis. We also detail the clinical application of these microfluidic chips in the liquid biopsy of various cancers.